2012
DOI: 10.1002/btpr.1565
|View full text |Cite
|
Sign up to set email alerts
|

Purification of IgG and albumin from human plasma by aqueous two phase system fractionation

Abstract: The current shortages in human plasma products at global levels justify the development of new, cost effective plasma fractionation methods. We have developed a fractionation process to obtain immunoglobulin G (IgG) and albumin-enriched fractions based on polymer-salt aqueous two phase system (ATPS). A small-scale (0.02 L) ATPS composed of polyethyleneglycol 3350 (PEG), potassium phosphate and sodium chloride, at pH 6.1, was evaluated and subjected to 50-fold scale-up (1 L). Further purification of the fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 44 publications
2
31
2
3
Order By: Relevance
“…Compared to the results presented by Vargas et al [21] for human plasma, a similar behavior was observed between fractionation of human and equine plasma in ATPS. Fig.…”
Section: Evaluation Of Purification Proceduressupporting
confidence: 89%
See 2 more Smart Citations
“…Compared to the results presented by Vargas et al [21] for human plasma, a similar behavior was observed between fractionation of human and equine plasma in ATPS. Fig.…”
Section: Evaluation Of Purification Proceduressupporting
confidence: 89%
“…A modification of the procedure for IgG purification from human plasma described by Vargas et al [21] and by the patent application document WO2012136172A1 [24] was employed. A diagram of the methodology is presented in Fig.…”
Section: Antivenom Purification By Atpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em alguns casos, a presença de IgM é citada nos processos de produção descritos para IgG VARGAS et al, 2012;VARGAS et al, 2015;WU et al, 2014 Neste trabalho nós propomos utilizar as mesmas técnicas utilizadas por Jehanli e Hough, uma gel filtração seguida de uma troca aniônica. Entretanto, a coluna de gel filtração utilizada neste trabalho, a Sepharose 4 FF, é para uso industrial e podemos aplicar de 20 a 25% volumes de coluna de amostra.…”
Section: Cadeia Pesada Iggunclassified
“…Alguns trabalhos descritos na literatura visam a purificação de IgG e albumina (FOURCART et al, 1982;GRELLET et al, 2001;VARGAS et al, 2012), mas não há nenhuma descrição conhecida com foco na purificação de IgM. Também é conhecida da literatura a separação de IgG de IgM (BREEN et al, 2012;BRNE et al, 2007;WU et al, 2014).…”
Section: Discussão Geral Da Estratégia 2 Da Purificação De Igmunclassified